Description And Causes Of Having Work Engagement In Employees - Yuli Evitha; Resista Vikaliana; La Ode Sabaruddin; Adji Sapta; Fino Wahyudi Abdul (Yayasan Ilomata, 2021)
Work engagement is a positive view of an employee towards his work that is characterized by vigour, full involvement (dedication), and high concentration during work (absorption). This study aims to determine the description and causes of having employee engagement by exploring dimensions based on the definition of work engagement proposed by Schaufeli, Gonzalez, & Bakker (2002), vigour, dedication, absorption. The research was conducted through a literature study that is finding various related sources and making conclusions in accordance with the research objectives. The credibility test used is peer debriefing, namely asking other researchers who are not involved in the research project to help investigate the thinking of researchers in all or certain parts of the research process. The results showed that the most dominant dimension of work engagement was dedication